The effect of HCl and steam on cyclic CO2 capture performance in calcium looping systems - Symonds, Robert T.; Lu, Dennis Y.; Macchi, Arturo; Hughes, Robin W.; Anthony, Edward J. (Elsevier, 2017)
Calcium looping is CO2 capture technology that is considered to be technically feasible at an industrial scale using a variety of fuels such as natural gas, coals, biomass, refuse derived fuels, and biofuels. Unfortunately, many of these fuels contain significant quantities of chlorine which principally converts to gaseous HCl during combustion or gasification. To date, very few studies have examined the effect of HCl on sorbent CO2 capture performance using calcium-based sorbents under realistic carbonation and calcination conditions. In this work, experiments were conducted using thermogravimetric analysis and fixed bed reactor testing to determine the effect of HCl addition during carbonation and calcination over repeated cycles using a Canadian limestone. The presence of HCl was found to increase sorbent reactivity towards CO2 capture when steam was injected during calcination. The resulting decomposition of CaCl2 to CaO during calcination caused changes in the particle morphology, which in turn decreased the CO2 diffusional resistance during carbonation. Fixed bed test results provided confirmation of full sorbent dechlorination under typical oxy-fuel calcination conditions. It was shown that both particle surface area and pore volume were higher during tests where HCl was present during carbonation and that greater than 99% HCl capture could be achieved without adversely affecting sorbent CO2 capture performance when steam was present during both carbonation and calcination.
Keywords: CO2 capture; HCl capture; Calcuim looping; Calcium base sorbent